Pengaruh Rasio Keuangan, Firm Size, dan Cash Flow terhadap Financial Distress - Wahyudi, Belva Monica; Trisnawati, Ita (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research aims to obtain empirical evidence regarding the influence of return on assets, current ratio, debt to equity ratio, firm size, total asset turnover, working capital to total asset ratio, and operating cash flow on financial distress. The sample of this research are cyclical and non-cyclical companies listed in Indonesia Stock Exchange between 2020-2022, and regularly issuing financial reports in Indonesian Rupiah. There are 179 companies with 537 data that selected as a final research sample and using a purposive sampling method for data processing. The obtained research results show that the current ratio influence financial distress. Other variables such as return on assets, debt to equity ratio, firm size, total asset turnover, free cash flow, working capital to total asset ratio, and operating cash flow do not influence financial distress.